GAMBARAN TEKANAN DARAH SISTOLIK, TEKANAN DARAH DIASTOLIK, TINGKAT HIPERTENSI, SERTA NILAI FECAL INCONTINENCE SEVERITY INDEX PADA KELOMPOK LANJUT USIA - Sutanto, Hari; Firmansyah, Yohanes; Satyanagara, William Gilbert; Kurniawan, Joshua; Yogie, Giovanno Sebastian; Destra, Edwin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Tarumanagara, 2023)
Fecal incontinence is a common problem faced by adults, which can cause psychosocial distress. Many risk factors, including patient’s comorbidities such as hypertension, increase the risk of fecal incontinence. The purpose of this study is to investigate the relationship between blood pressure, hypertension levels, and FISI in the elderly patients. This research is a cross-sectional study that conducted at Santa Anna nursing resident from June-July 2023. The sampling method used was total sampling. There were 60 respondents who met the criteria, which were dominated by women as many as 40 (66.7%). On the scatter plot, it was found that systolic blood pressure of 160mmHg and diastolic blood pressure of 100mmHg produced a liner consistency value with the severity of fecal incontinence. Hence health workers need to assess patients thoroughly, especially comorbidities when dealing with elderly people with fecal incontinence, to ensure a well-maintained quality of life for the patient.